2016
DOI: 10.1177/0954406216656886
|View full text |Cite
|
Sign up to set email alerts
|

Induced-charge electro-osmotic flow around cylinders with various orientations

Abstract: Induced-charge electro-osmosis around multiple gold-coated stainless steel rods under various AC electric fields is investigated using the techniques of microparticle image velocimetry and numerical simulation. In this study, the results of interactions between induced electric double layers of two identical conductive cylinders on surrounding fluid are presented. The induced-charge electro-osmosis flow around multiple rods in touch and with one cylinder diameter gap reveals quadrupolar flow structures with fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…To this end, we present a numerical simulation study of active control on the transient growth of the ion depletion layer by driving ICEK streaming flows in present study, which resolves well the aforementioned defects for on‐chip nanofluidics‐based macromolecule sensing. In fact, the idea was originally proposed by Park and Yossifon .…”
Section: Introductionmentioning
confidence: 69%
“…To this end, we present a numerical simulation study of active control on the transient growth of the ion depletion layer by driving ICEK streaming flows in present study, which resolves well the aforementioned defects for on‐chip nanofluidics‐based macromolecule sensing. In fact, the idea was originally proposed by Park and Yossifon .…”
Section: Introductionmentioning
confidence: 69%
“…Besides the native EDL full of cations within the dielectric nanopore, the conducting nanochannel mounted at the pore entrance can be readily polarized by a DC electric field imposed along the channel length direction, which gives rise to additional induced counterions of a bipolar nature under the covering region of the metal pore via the physical principle of induced-charge electrokinetics (ICEK) (Figure 2b,c) [65][66][67][68][69][70][71][72][73]. Namely, more cations than anions are induced on the anodic side of the conducting wall, while excessive anions are induced on the cathodic side of the conducting channel, regardless of the specific polarity of the applied DC bias (Figure 2b,c).…”
Section: Chip Geometry and Device Operation Principlementioning
confidence: 99%
“…Because the ionic charge layer emerges as a result of the applied AC electric field, both the induced free charge and tangential field component are sinusoidal functions of the time variable under Debye-Huckel limit, resulting in time-averaged electroosmosis flow even in a harmonically oscillating field [ 23 , 24 , 25 ]. Later, Bazant and Squires [ 26 , 27 ] indicated that a background electric field can act on its own induced free charge within the Debye layer at a polarizable phase interface, which is genuinely a more accurate physical description of nonlinear electrokinetic phenomena, and they coined the term ‘Induced-Charge Electroosmosis (ICEO)’ to delineate electroosmotic streaming on polarizable or highly-charged solid surfaces immersed in saline solutions, which has incorporated the physical concepts of AC electroosmosis/traveling-wave electroosmosis (ACEO/TWEO) on driving electrodes in standing-wave [ 28 , 29 ]/traveling-wave [ 30 , 31 , 32 , 33 , 34 , 35 ] electric fields, ICEO on bipolar conducting [ 15 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]/semiconducting [ 43 , 44 ]/dielectric [ 16 , 45 , 46 , 47 , 48 ] materials, and electroosmosis of second kind due to surface-conduction-induced bulk concentration polarization [ 49 , 50 , 51 , 52 ]. This new category of electrohydrodynamic flow shows great advantages in suppressing electrode reactions and bubble productions, as well as actuating faster fluid flows than conventional linear electroosmosis, by virtue of its second-order voltage dependence in time-varying electric fields [ 14 , 53 , 54 ,…”
Section: Introductionmentioning
confidence: 99%